(untitled) (Journal of Applied Learning and Teaching, 2020)
This case study tracks the entrepreneurial journey taken by female founder Sarah Kauss in developing a categorydefining premium drinking bottle. S’well was created using a low budget, word-of-mouth community and unpaid celebrity endorsement strategy. It was established as a fashion power brand through carefully crafted, high end, retail and charity collaborations. Historically, portable water storage had been framed as merely functional products. Former Manhattan accountant Sarah Kauss helped redefine the category as a modish accessory solution that also countered the environmental problem of disposable plastic waste, using a double organic business strategy. S’well has been flatteringly described by Vogue as a true original with a delicious Midas touch, and CNN as ‘hands down the best water bottle for temperature control’ (S’well.com, 2020). However, plagued by brand-damaging counterfeiters and losing traction from the historically powerful co-created social media promotions, was it time for an important third pivot? This armchair teaching case study was developed from the lead author’s digital marketing coursework, as part of the Royal Holloway BSc Management programme at Kaplan Singapore. The case was designed for use in marketing, strategy and entrepreneurship under- and postgraduate modules.